THE EFFECTIVENESS OF YOGA IN INCREASING THE LEARNING CONCENTRATION OF PRESCHOOL CHILDREN AT THE NATIONAL KINDERGARTEN IN LAU TIMAH VILLAGE - Novita Rifka; Eka falentina tarigan; Marliani; Rosmani Sinaga; Tetti Seriati Situmorang; widia rapika, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Preschool children mean the basis of development in children, including attitudes, knowledge, skills, creativity and adjustment of their social environment. Based on the 2018 Riskesdas, a comparison of the development of children at the age of 36-59 months in Indonesia with a total development index of 88.3%, where 64.6% literacy, 97.8 5 development 88.3, where 64% literacy, 97.8% physical, 69 ,9% social emotional, and 95,2% learning. Obstacles that occurred during the Covid-19 pandemic, students had difficulty concentrating on studying from home and complained about the difficulty of assigning questions from teachers, increasing pressure and boredom due to continuous isolation, which has the potential to cause anxiety and depression for children. Research to determine the effect of children's yoga on the concentration of learning in preschool children. Methods: The population and sample in this study were kindergarten students with a total of 40 students, 20 students for the experimental group, and 20 students for the control group. This study uses a quasi-experimental research design of Non Equevalent Control Grub Design . The parametric hypothesis test is the paired sample t-test. The test results stated that there was a difference in the level of concentration in learning after being given the child's yoga treatment.